Correlation Between Computer Self-Efficacy Belief and Computer Value Belief during the New Normal - Almila Amihan R. Borinaga; Rodulfo T. Aunzo (Newinera Publisher, 2021)
In the light of the New Normal, the students' attention has moved to computer technology. Thus, this research study investigated the VSU-Isabel students' computer self-efficacy and computer value during the New Normal. The study employed quantitative-descriptive research utilizing the mean and standard deviation of the students' responses in the survey items. It also employed a correlational approach in establishing the relationship between students' computer self-efficacy and computer value. A convenience sampling technique was used to arrive at a sample of 687 student-respondents from 1st year to 5th year. The research study revealed that the students are undecided if they can use computers compared to the other students. Also, it was found out that students agreed about the value of computers. Additionally, the study revealed that there is a significant and low positive correlation, r (685) = .387, p = .01, between the students' computer self-efficacy belief and computer value belief during the New Normal. These findings recommend the expanded use of technology during the new normal such as using different available digital platforms to develop the computer self-efficacy of the students.